2023
DOI: 10.3390/land12020498
|View full text |Cite
|
Sign up to set email alerts
|

Creative Tourism in Islands and Regional Sustainable Development: What Can We Learn from the Pilot Projects Implemented in the Azores Territory?

Abstract: The current need for territories and societies to grow is based on the Sustainable Development Models as well as the United Nations (UN) Agenda for 2030 Sustainable Development Goals (SDGs). In that case, such new forms of tourism development imply creating and upgrading critical infrastructures, facilities, equipment, or differentiated activities to bring clients who align with the desired Sustainable Development Models and SDGs. In this regard, the thematic literature provides evidence that some tourism typo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Rui Alexandre Castanier, Carlos Santos, Igualter [7] found that some typologies of tourism (natural, rural, cultural and creative tourism) play a crucial role in achieving sustainable regional development, regional leaders can consider promoting entrepreneurship related to small and medium-sized firms; promoting the diversity of tourism offerings.…”
Section: Discussionmentioning
confidence: 99%
“…Rui Alexandre Castanier, Carlos Santos, Igualter [7] found that some typologies of tourism (natural, rural, cultural and creative tourism) play a crucial role in achieving sustainable regional development, regional leaders can consider promoting entrepreneurship related to small and medium-sized firms; promoting the diversity of tourism offerings.…”
Section: Discussionmentioning
confidence: 99%
“…ccording to UNWTO, travelers are becoming more attracted to different tourism typologies (mainly rural or nature based), because they look for less crowded places with outdoor spaces (Castanho et al, 2023). Based in the table, several mapping tourist villages in Gianyar district have major tourism potential based on natural beauty which offers natural beauty in the form of beaches, waterfalls and rice fields (subak).…”
Section: Nature-based Creative Tourism Village Developmentmentioning
confidence: 99%
“…Currently, there is a lack of empirical studies that have examined the impact of the integration of the culture industry and tourism on regional green development. Some studies have extensively examined the influence of tourism on regional sustainable development [22,23] and the efficiency of urban green development [24,25] from a tourism economic perspective. Alternatively, separate analyses have been conducted on the economic growth driven by the cultural and tourism industries [8,18].…”
Section: Introductionmentioning
confidence: 99%